Generation of Sunward Ion Cyclotron Waves and the Nature of Right-handed Polarized Ion-scale Waves in the Near-Sun Solar Wind - Chen Shi; Jinsong Zhao; Yifan Wu; Si Liu; Fuliang Xiao; Huasheng Xie (The Astrophysical Journal)
Observations from the Parker Solar Probe have revealed the ubiquitous presence of right-handed polarized waves in the near-Sun solar wind. While antisunward fast-magnetosonic whistler waves have been commonly considered as their source, sunward ion cyclotron waves (ICWs) are another plausible candidate. Sunward ICWs can directly interact with antisunward ions via cyclotron resonant interactions, suggesting they may play an important role in particle energization processes in the solar wind. However, the generation of sunward ICWs remains poorly understood. In this study, we perform a theoretical instability survey over a broad parameter space to investigate the conditions that favor the generation of sunward ICWs, focusing on two key plasma properties: the temperature anisotropy and the relative streaming speed of the proton beam component. Our results show that sunward ICWs can be excited by proton beams with slow streaming speeds but significant temperature anisotropy. Additionally, the analysis reveals that the growth of this instability is strongly suppressed in environments with high alpha particle concentrations, indicating that sunward ICWs preferentially arise in plasmas with low alpha particle abundance. These findings offer new insights into the generation and nature of ion-scale waves in the near-Sun solar wind.